Portable Video Magnification Solutions for the Low Vision Prescriber. - Smith, Emily; Zerilli-Zavgorodni, Theresa; Shenouda-Awad, Nancy (Optometry & Visual Performance, 2022)
Background: Video magnification (VM) is a useful tool often employed in low vision rehabilitation (LVR), particularly when conventional magnification options are unable to fulfill a patient's reading goals. VM offers an alternative solution to overcoming the limitations of traditional low vision (LV) aids. Portability is an important feature that can extend the use of these devices into multiple settings and tasks. As with any LV aid, every portable VM device will have pros and cons that should be considered when prescribing. Case Reports: Five cases are discussed illustrating the application of a systematic approach to prescribing portable VM devices for LV patients with various levels of visual impairment. Standard measures of visual function, including visual acuity (VA), visual fields (VF), and contrast sensitivity, were reduced to different extents in each case. All patients communicated a chief complaint of decreased reading performance. Primary goals covered included spot reading, recreational volume reading, and vocational reading. These goals were all successfully met by carefully matching each patient's reading goals with a specific type and model of a portable VM device. Conclusion: Handheld VM devices offer a portable and adaptable solution for addressing a LV patient's reading needs, thereby making these devices appealing to both the LV provider and the patient. However, with such a large array of portable electronic magnifiers available on the market, the task of prescribing the most appropriate device for the LV patient can be challenging. A systematic LVR approach assessing all of the factors that may influence a patient's success with a portable VM device can ease the selection process. This paper will provide an overview of the vast number of options of portable VM devices available, review the patient and device selection criteria utilized for determining the most appropriate one, and demonstrate practical application of these devices in LVR through case presentation.